A 2020 Update on 20/20 X 2: Diplopia after Ocular Surgery Diplopia after Iatrogenic Monovision. Issue 4 (2nd October 2021) - Jackson, Jorie
ABSTRACT: Monovision is a scenario in which anisometropia is artificially induced to allow a presbyopic patient to see at both distance and near. This will create a situation where one eye is always blurred at either distance. In most cases, the dissimilar images projecting onto the two foveas are well tolerated by the patient. However, in some cases, the two images can be so dissimilar in clarity that the brain cannot fuse the two images and the patient will complain of binocular vision issues such as diplopia. Learning how to predict post-operative diplopia in high-risk patients will improve surgical outcomes.